Long-Term Effect of Bariatric Surgery on Liver Enzymes in the Swedish Obese Subjects (SOS) Study - Burza, Maria Antonella; Romeo, Stefano; Kotronen, Anna; Svensson, Per-Arne; Sjöholm, Kajsa; Torgerson, Jarl S.; Lindroos, Anna-Karin; Sjöström, Lars; Carlsson, Lena M. S.; Peltonen, Markku (PloS one, 2013)
Obesity is associated with elevated serum transaminase levels and non-alcoholic fatty liver disease and weight loss is a recommended therapeutic strategy. Bariatric surgery is effective in obtaining and maintaining weight loss. Aim of the present study was to examine the long-term effects of bariatric surgery on transaminase levels in obese individuals. The Swedish Obese Subjects (SOS) study is a prospective controlled intervention study designed to compare the long-term effects of bariatric surgery and usual care in obese subjects. A total of 3,570 obese participants with no excess of alcohol consumption at baseline (1,795 and 1,775 in the control and surgery group, respectively) were included in the analyses. Changes in transaminase levels during follow-up were compared in the surgery and control groups. Compared to usual care, bariatric surgery was associated with lower serum ALT and AST levels at 2- and 10- year follow up. The reduction in ALT levels was proportional to the degree of weight loss. Both the incidence of and the remission from high transaminase levels were more favorable in the surgery group compared to the control group. Similarly, the prevalence of ALT/AST ratio <1 was lower in the surgery compared to the control group at both 2- and 10-year follow up. Bariatric surgery results in a sustained reduction in transaminase levels and a long-term benefit in obese individuals.